Disappearance of Seasonal Respiratory Viruses in Children Under Two Years Old During COVID-19 Pandemic: A Monocentric Retrospective Study in Milan, Italy - Ippolito, Giulio; La Vecchia, Adriano; Umbrello, Giulia; Di Pietro, Giada; Bono, Patrizia; Scalia Catenacci, Stefano; Pinzani, Raffaella; Tagliabue, Claudia; Bosis, Samantha; Agostoni, Carlo; Marchisio, Paola Giovanna (Frontiers in Pediatrics, 2021)
Background: the containment measures adopted during COVID-19 pandemic have influenced the epidemiology of other respiratory viruses Aim: we analysed the modification of the incidence and aetiology of lower respiratory tract infections (LRTIs) in young children during COVID-19 pandemic Methods: case series of all children under two years old hospitalized at a tertiary care Hospital in the Center of Milan, Italy diagnosed with LRTIs in three consecutive winter seasons (from the 1st of November to the last day of February in 2018/2019, 2019/2020 and 2020/2021). We compared the number of hospitalizations and viral detections in the 2020/2021 with the average of 2018/2019 and 2019/2020 (pre-COVID-19) using the Poisson distribution Results: we enrolled 178 patients (66 from 2018/2019, 96 from 2019/2020, 16 from 2020/2021) 94 males (53%) and 84 females (47%), with a median (IQR) age of 5 (2-13) months. The number of hospitalizations during the 2020/2021 season was 80% lower than the average of the pre-COVID-19 seasons (16 vs 81, p<.001). Overall, 171 (96%) patient’s nasopharyngeal aspirate (NPA) detected at least one virus (110, 64%, single-detection, 61, 36%, co-detections). In 2020/2021 we observed the disappearance of Respiratory Syncytial virus (0 vs 54, p<.001), Influenza virus (0 vs 6.5, p=.002), Metapneumovirus (0 vs 8, p<.001), Parainfluenza viruses (0 vs 3.5, p=.03) and a significant reduction of Adenovirus (2 vs 7, p=.03), Bocavirus (2 vs 7.5, p =.02) and Enterovirus (1 vs 5, p=.04). No significant difference was found for Rhinoviruses (14 cases vs 17, p=.2), other Coronaviruses (0 vs 2, p=.1), and Cytomegalovirus (1 vs 1, p=.7). Conclusions: we observed a striking reduction in hospitalizations due to LRTIs and a modification of the aetiology, with enveloped viruses mainly affected